Head acceleration measurement techniques: Reliability of angular rate sensor data in helmeted impact testing. (June 2018) - Cobb, Bryan R; Tyson, Abigail M; Rowson, Steven
This study sought to evaluate the suitability of angular rate sensors for quantifying angular acceleration in helmeted headform impacts. A helmeted Hybrid III headform, instrumented with a 3-2-2-2 nine accelerometer array and angular rate sensors, was impacted (n = 90) at six locations and three velocities (3.1, 4.9, and 6.4 m/s). Data were low-pass filtered using Butterworth four-pole phaseless digital filters which conform to the specifications described in the Society of Automotive Engineers J211 standard on instrumentation for impact tests. Nine accelerometer array data were filtered using channel frequency class 180, which corresponds to a −3 db cutoff frequency of 300 Hz. Angular rate sensor data were filtered using channel frequency class values ranging from 5 to 1000 Hz in increments of 5 Hz, which correspond to −3 db cutoff frequencies of 8 to 1650 Hz. Root-mean-square differences in peak angular acceleration between the two instrumentation schemes were assessed for each channel frequency class value. Filtering angular rate sensor data with channel frequency class values between 120 and 205 all produced mean differences within ±5%. The minimum root-mean-square difference of 297 rad/s 2 was found when the angular rate sensor data were filtered using channel frequency class 175. This filter specification resulted in a mean difference of 28 ± 297 rad/s 2 (1.8% ± 8.6%). Condition-specific differences (α=0.05) were observed for 11 of 18 test conditions. A total of 4 of those 11 conditions were within ±5%, and 10 were within ±10%. Furthermore, the nine accelerometer array and angular rate sensor methods demonstrated similar levels of repeatability. These data suggest that angular rate sensor may be an appropriate alternative to the nine accelerometer array for measuring angular head acceleration in helmeted head impact tests with impactor velocities of 3.1–6.4 m/s and impact durations of approximately 10 ms.